METHODS OF REDUCING THE ENERGY CONSUMPTION OF PRODUCTS IN LIGHT INDUSTRY ENTERPRISES - Tursunov, A.Sh. (Educational Research in Universal Sciences, 2023)
In these studies, very little attention has been paid to options for reducing thermal energy loss in buildings due to the implementation of structural and engineering-technical energy saving measures. Despite the fact that these measures have great potential for energy savings, taking into account the climatic features of the zoning of textile and light industrial enterprises. Energy resources are spent not only directly on the production of finished products, but also on the raw materials used in their production. At the same time, energy is spent not only on the production of materials and products, but also on the maintenance of production and public buildings, maintaining standard microclimate parameters and favorable production conditions in them.